The Depp blue sea - Wood, Audrey (New York : Scholastic, 2005)
Readers will love learning their colors with this brightly illustrated, cumulative picture book by bestselling author Audrey Wood and her dynamic, digital-artist son, Bruce. Starting with a rock, a red rock, in the middle of the deep blue sea, the story takes a closer look at this tropical locale. The simple, repetitive text makes for a fun read-aloud for story time or sharing, and identifying the vivid images and strong colors provides an exciting concept learning experience for young readers.